Impulse Buying of MSME Instant Food Products: A Stimulus-Organism-Response Approach Among Urban Consumers in Greater Jakarta - Aryono Kurnianto; Ependi Ependi; Agus Rizal (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid growth of the instant food Micro, Small, and Medium Enterprises (MSME) sector in Indonesia has increased the importance of understanding consumer impulse buying behavior in this market. This study aims to examine the influence of external stimuli on impulsive buying urge and impulse buying behavior using the Stimulus–Organism–Response (S-O-R) framework. A quantitative approach was employed by collecting data from 221 consumers in the Greater Jakarta area through a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that marketing and promotional stimuli, product characteristic stimuli, and shopping environment and social stimuli significantly influence impulsive buying urge, with marketing and promotional stimuli emerging as the strongest predictor. In addition, impulsive buying urge has a significant positive effect on impulse buying behavior. The results further reveal that the direct effects of external stimuli on impulse buying behavior are insignificant, whereas their indirect effects through impulsive buying urge are significant, indicating a full mediation mechanism. These findings confirm that impulsive buying urge serves as the primary psychological mechanism linking external stimuli to actual purchasing behavior. The study contributes to the extension of the S-O-R framework in the context of MSME instant food products and provides practical insights for developing marketing strategies that effectively stimulate impulse purchases through urgency-oriented promotional activities.